Graft uptake and post-operative hearing outcome with type-I tympanoplasty in dry versus wet ear: a comparative study - Sandhu, Kulwinder Singh; Kaur, Puneet; Singh, Jagdeepak; Arya, Sania (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: The discharging ear presents the otologist with the dilemma of operating on it or not. This study is being undertaken to study and compare the results of type I tympanoplasty in dry ear (no ear discharge at the time of surgery) and wet ear (culture negative consistent ear discharge at the time of surgery). Methods: 50 patients of either sex aged between 18 to 50 years undergoing type-I tympanoplasty were included in the study on the basis of pre-determined clinical criteria. Type I tympanoplasty was performed using temporalis fascia graft by underlay technique. Post-operative data regarding graft uptake and hearing improvement was recorded in the follow up period of three months. Results: The complete graft uptake was there in 88% of the patients in group 1 and 84% patients in group 2. The difference in the two groups was statistically insignificant (p>0.05). The mean pre-operative pure tone average in group 1 was 30.57±7.80 dB while post-operative pure tone average was 20.68±8.22 dB with a mean hearing gain of 9.89 dB. The mean pre-operative pure tone average in group 2 was 35.21±5.98 dB while the post-operative pure tone average was 27.07±9.25 dB with a mean hearing gain of 8.12 dB. There was marked hearing improvement in both the groups post operatively (p<0.001 i.e., highly significant). When hearing improvement was compared between two groups there was no significant statistical difference (p>0.05). Conclusions: The outcome is equally good for type 1 tympanoplasty in dry and wet ear in safe (mucosal) type of chronic suppurative otitis media with respect to graft uptake and hearing improvement.